Rice Husk Waste: Impact on Environmental Health and Potential as Biogas (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Indonesia is an agricultural country with dry-milled grain production reaching 55.6 million tons in 2022. Besides producing an abundance of rice, milled dry rice also results in waste in the form of rice husks. The handling of rice husk waste is mostly by burning. The smoke from burning is toxic, so it has a poor impact on environmental health. This study is regarding the effect of improper management of rice husks on environmental health, the utilization of rice husks in biogas energy, and its potential in Indonesia. Air quality measurement in areas burning rice husks on the parameters SO2, CO, NO2, and PM10 regarding the method of the Indonesian National Standard. Then anaerobic laboratory-scale research to convert rice husk into biogas. Chemical pretreatment was carried out with 3% NaOH and the C/N ratio determined was 25. Condition variations were determined for L-AD with 7% TS and SS-AD with 17% TS. We found that burning rice husks harm on environmental health. It is indicated by the SO2 and PM10 parameters exceeding the quality standards, namely 167 and 132 µg/m3.The NO2 parameter almost reached the quality standard, namely 178 µg/m3. Generated rice husk can be converted into renewable energy in biogas with good productivity in SS-AD conditions, with biogas production reaching 75.2 mL.gTS-1. Biogas potential from rice husks reached 1.5 million liters. It can support energy security for Indonesia.